Shape optimisation problem for stability of Navier–Stokes flow field. Issue 2 (16th March 2018) - Kiriyama, Yasuyuki; Katamine, Eiji; Azegami, Hideyuki
ABSTRACT: This paper presents the numerical results of a shape optimisation problem with regard to delaying the transition of a Navier–Stokes flow field from laminar to turbulent by using the theory developed by Nakazawa and Azegami. The theory was reviewed within the framework of functional analysis and updated with another expression of the shape derivative with respect to the objective function. A computer program was developed with the FreeFEM++. Numerical analyses were performed for two types of problems: a two-dimensional Poiseuille flow field with a sudden expansion and a two-dimensional uniform flow field around an isolated body. From the first example, two local minimum points of symmetric and asymmetric flow fields were determined, and the asymmetric flow field was found to be more stable. With regard to the second example, we reached the local minimum point of an elliptical shape, and infrequently determined a solution converging to an elliptical shape with the bluff in the leeward direction. By comparison, the superiority of the elliptical shape was obvious.